ESPAC-based 2D mini-array microtremor method and its application in urban rail transit construction planning. (September 2021) - Xu, Peifen; Ling, Suqun; Long, Gang; Qiao, Gaoqian; Shen, Qiuhua; Yao, Jin; Zhang, Hua
Highlights: Microtremor method. Microtremor profile survey using mini-array and apparent S-wave velocity imaging. ESPAC method. Rayleigh wave. Geophysical method in urban rail transit survey and urban geological investigation. Abstract: Conventional geophysical methods face many challenges in urban areas from limited site accessibility to severe industrial interferences. With the fast-paced development in urban area and urban light rail transit system, it is highly desirable to have a high-resolution geophysical method, which is suitable for the complex urban condition with strong background noises and, at the same time, is environment-friendly. In this paper, we introduce a 2D mini-array microtremor survey method, based on the extended spatial auto-correlation (ESPAC) method. It first uses the ESPAC to extract the dispersion curve of the Rayleigh wave from the microtremor data recorded using the mini array, then reconstructs the apparent S -wave velocity ( Vx ) structure of the stratigraphic rock formations by the Vr – Vx transformation, and finally, the 2D Vx profile is obtained by using Vx velocity imaging. This method not only makes full use of the multi-mode Rayleigh waves of dispersion curve, but also reduces the uncertainty during inversion caused by the potential pattern misjudgment when inverting the dispersion curve directly. Since the Vx is generally sensitive to the change of rock mass density, its profile is a natural and reliable reflection of the changes in rock properties. This technique provides an accurate and cost-effective tool for mapping complex near-surface geological anomalies such as karst cavities, fractured zone, and the soil/bedrock interface, which are frequently encountered in many urban engineering projects, such as urban rail transit development. The successful application of the microtremor survey in Guangzhou Metro Line 10 project demonstrates that this method can be very effective in identifying the soil/bedrock interface, mapping the severely weathered rock formations, and detecting the abandoned underground structures.